Green Human Resource Management: An Empirical Study of India - Arora Mamta; Kaul Arpita (Visegrad Journal on Bioeconomy and Sustainable Development, 2020)
Purpose: The broad over-arching goals of this work were to study the existing constituents of green human resource management (HRM), to understand the green HRM practices being followed by different companies in India (belonging to certain sectors) and to compare the different sectors in terms of adoption of green HRM. Methodology: A questionnaire was meticulously prepared by the authors to collect the data for this study and was sent to various Indian companies belonging to four sectors: IT/IT services, banking/finance, consultancy and engineering/technology. The questionnaire included a carefully selected collection of questions to gain rich insights into different aspects of green HRM implementation. Findings: most of the companies included in this study are following green HRM (though to varying extents). Green recruitment, green training and development & green safety and health management are the most prominent green HRM functions while green performance appraisal is the least popular green HRM function among these organizations. The IT/IT services sector is most actively using green HRM practices while the banking/finance sector is the most reluctant to adopt green HRM. Practical Implications: a rigorous structure for companies to implement green HRM is provided.